EVALUASI SALURAN DRAINASE DAN PENANGANAN GENANGAN AIR DI JALAN PENGGING-BANYUDONO KABUPATEN BOYOLALI - Putra, Gian Rahmanda; Wijayanti, Paska; Sumina, Sumina (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
A drainage system is a series of activities designed to drain water from an area or area, including surface water and ground water. Drainage systems are also an important part of urban areas. A well-organized urban area must have a drainage system that functions well, so that it does not cause standing water which can disrupt community activities, especially those related to environmental health. On the Pengging-Banyudono road, Ngaru-ngaru Village, Banyudono District, Boyolali Regency, which is a residential area and sales kiosk, there are still several problems with the drainage system which is not functioning properly and must be addressed immediately. If the rainfall is high enough, it will cause water to pool on the body and shoulders of the road, which can cause water channels to become blocked and disrupt residents' activities. So it is necessary to evaluate drainage channels and handle waterlogging on Jalan Pengging-Banyudono, Boyolali Regency. This research aims to determine the existing drainage system and evaluate the capacity of the drainage channel. From monitoring, there is sedimentation, sedimentation and changes in the cross-sectional dimensions of the channel which trigger blockage of water flow. Meanwhile, the analysis results show that the channel capacity is unable to accommodate the existing flood discharge. In the existing channel, the channel discharge (Qs) is 0.0081m3/second, smaller than the 25 year flood discharge (0.2783 m3/second). This means that the existing channel capacity is not able to accommodate flood discharge. The results of calculating the dimensions of the new channel, obtained the most economical channel dimensions with a channel width of 1.2 m and a channel height of 1.2 m.